Phenylpropanoids and lignoids from the whole plant of Vaccinium emarginatum and their cytotoxicity against prostate cancer cells. Issue 12 (31st May 2021) - Tu, Ping-Chen; Liang, Yu-Chia; Kao, Ming-Ching; Chao, Louis Kuoping; Tseng, Mei-Hwei; Lu, Te-Ling; Sung, Ping-Jyun; Kuo, Yueh-Hsiung
Abstract: One new naturally occurring quinone, 3′, 4′-dihydroxy-1, 2, 6-trimethoxy-[1, 1′-biphenyl]-4(1 H )-one (1 ), one new diarylpropane, emarginone A (2 ), and one new neolignan, emarginone B (3 ), along with eighteen known compounds have been isolated from the chemical investigation of the EtOAc-soluble fraction of the Vaccinium emarginatum whole plant methanolic extract. The new structures were elucidated by combined analysis of spectroscopic analytical methods and comparison with the literature data obtained from known analogues. In addition, the cytotoxicity of compounds 2, 4, and 14–20 against Du145 and PC-3 prostate cancer cell lines using MTT cell proliferation assay was evaluated. Compounds 2 and 19 showed most potent cytotoxicity against Du145 with IC50 values of 7.53 and 6.63 μg/mL, respectively. Furthermore, compounds 2, 17, and 19 also exhibited significant cytotoxicity against PC-3 with IC50 values ranging from 3.44-6.64 μg/mL. Graphical Abstract: